Tandem Walk in Simulated Martian Gravity and Visual Environment - Rosenberg, Marissa J.; Koslovsky, Matthew; Noyes, Matthew; Reschke, Millard F.; Clément, Gilles (Brain sciences, 2022)
Astronauts returning from long-duration spaceflights experience visual-vestibular conflicts that causes motion sickness, perceptions that the environment is moving when it is not, and problems with walking and other functional tasks. To evaluate whether astronauts will have similar decrements after they land on Mars following exposure to weightlessness, participants were held by a device that offloads their weight, first entirely (0 G), and then partially (0.38 G) or not at all (1 G). Tandem (heel-to-toe) walk on a medium-density foam surface was used to assess the subject’s walking performance. Two visual conditions in virtual reality were investigated: normal vision and a visual-vestibular conflict generated by disorienting optokinetic stimulation (DOS). Tandem walking performance with DOS was better in 0.38 G compared to 1 G. Tandem walking performance in DOS in 1 G was not significantly different from tandem walking performance after spaceflight or bed rest. The increased tandem walking performance in 0.38 G compared to 1 G was presumably due to an increased cone of stability, allowing a larger amplitude of body sway without resulting in a fall. Tandem walking on a compliant foam surface with a visual-vestibular conflict is a potential analog for simulating postflight dynamic balance deficits in astronauts.